Characterization of cDNA for PMT: a Partial Nicotine Biosynthesis-Related Gene Isolated from Indonesian Local Tobacco (Nicotiana tabacum cv. Sindoro1) - SESANTI BASUKI; NURHAJATI MATTJIK; DESTA WIRNAS; . SUWARSO; . SUDARSONO (Bogor Agricultural University, Indonesia, 2013)
Nicotine is the major alkaloid compound in cultivated tobacco (Nicotiana tabacum) that could potentially be converted into carcinogenic compound (nor-nicotine). The PMT gene encoding putrescine N-methyltransferase (PMT) is one of the two key genes that play a prominent role in nicotine biosynthesis. The aimed of this study was to isolate and characterize the cDNA sequence originated from Indonesian local tobacco cv. Sindoro1 (Ntpmt_Sindoro1). The results showed that the Ntpmt_Sindoro1 was 1124 bp in length. This cDNA fragment encodes for 374 amino acid residues. The predicted polypeptide from the cDNA is a hidrophilic protein, and has a predicted molecular weight of 40.95 kDa. The predicted amino acids sequence also showed high similarity to the PMT gene product Nicotiana sp. available in the GenBank data base. The amino acid sequences also exert conserved residues specifically exhibited only by PMT gene originated from N. tabacum. Clustering analysis revealed that Ntpmt_Sindoro1 belongs to the same clade as the PMT3 gene, a member of the N. tabacum PMT gene family. The Ntpmt_Sindoro1 cDNA sequence covering exon1-exon8 of the PMT gene fragment has been registered in the GenBank data base, under the accession number JX978277.